21st Century Learning: 4C Skills In Case Method And Team Based Project Learning - Peny Husna Handayani; Sariana Marbun; Dwi Maya Novitri (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2023)
The life of the 21st century presents its own challenges in the world of education, namely how in the learning process students are provided with skills to survive in the global world of the 21st century. The purpose of this study is to describe how well the 2nd century (4C) skills possessed by Early Childhood Education Teacher students are in case-based lectures and team based projects. The approach used in this research is quantitative and the method used is descriptive. The sample in this study were 2nd, 4th, and 6th semester students, totaling 450 students. The data collection technique is through filling out questionnaires about 4C skills which are carried out by self and peer assessment online by students. The results show that students' critical thinking and creativity are in the good category with an average critical thinking score of 83.7 and creativity of 85.4. Meanwhile, the communication (87.4) and cooperation skills (89.7) of students are in the very good category. Case-Method and team-based projects learning can help develop 4C skills as 21st century skills.Keywords:Â 21st century learning, critical thingking, creativity, communication, collaboration, 4C skills